The Relationship Between Caring Leadership and Nurse Job Satisfaction at dr. R. Goeteng Taroenadibrata Purbalingga Hospital - Siti Khofifah; Tri Sumarni; Indri Heri Susanti (Universitas Ibn Khaldun Bogor, 2023)
Nurses as health workers who play an important role in determining the quality of service in hospitals must be managed properly, one of which is by providing job satisfaction. The style or behavior of the leader greatly affects his subordinates. The leader's caring behavior toward subordinates or employees is called caring leadership. The purpose of this study was to determine the relationship between caring leadership and nurse job satisfaction at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The research method used is descriptive correlation using a cross-sectional design. The sampling technique uses purposive sampling with a total sample of 96 nurses. Research instruments. using the Caring Factor. Survey-Caring of Manager (CFS-CM) is a caring leadership questionnaire and Minnesota Satisfaction Questionnaire (MSQ) is a job satisfaction questionnaire. The analysis used Kendall's Tau-b (Ʈ) correlation test. The results obtained caring leadership in the medium category were 64 respondents (66.7%) and nurse job satisfaction in the medium category was 52 respondents (54.2%). The results of statistical tests using Kendall's Tau-b (Ʈ) obtained a calculated p-value of 0.0396 (p < 0.05). The conclusion is that there is a meaningful relationship between caring leadership and nurse job satisfaction at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. It is recommended that nurses maintain and improve their ability to provide nursing care to patients so that job satisfaction can be met. Nurses are also expected to be active in providing input to management on the criteria for a good head of space so that nurses' job satisfaction increases.